Nitrifying–denitrifying filters and UV-C disinfection reactor: a combined system for wastewater treatment. Issue 6 (19th March 2017) - Ben Rajeb, Asma; Mehri, Inès; Nasr, Houda; Najjari, Afef; Saidi, Neila; Hassen, Abdennaceur
ABSTRACT: Biological treatment systems use the natural processes of ubiquitous organisms to remove pollutants and improve the water quality before discharge to the environment. In this paper, the nitrification/denitrification reactor allowed a reduction in organic load, but offered a weak efficiency in nitrate reduction. However, the additions of the activated sludge in the reactor improve this efficiency. A decrease of values from 13.3 to 8 mg/l was noted. Nevertheless, sludge inoculation led to a net increase of the number of pathogenic bacteria. For this reason, a UV-C pilot reactor was installed at the exit of the biological nitrification–denitrification device. Thus, a fluence of 50 mJ.cm -2 was sufficient to achieve values of 20 MPN/100 ml for fecal coliform and 6 MPN/100 ml for fecal streptococci, conforms to Tunisian Standards of Rejection. On the other hand, the DGGE approach has allowed a direct assessment of the bacterial community changes upon the treated wastewater.